Development of German Grammar Textbook Based on Metacognical Skills - Mantasiah R; Andi Tenri Ola Rivai; Yusri Yusri; Muhammad Anwar (Makassar State University, 2021)
Abstract. Strukturen Und Wortschatz Material (German grammar) is one of the difficult materials for students to understand. Therefore, efforts are needed to improve the quality of learning in these courses so that students can easily understand the material in these courses. The purpose of this study was to determine the validity of the textbook based on metacognitive abilities that had been developed. This study uses a Research and Development approach. Research respondents consisted of expert validators (German lecturers and teachers) and students as user validators. Based on the results of the validity test, the book developed is valid. In addition, based on the public test of the response of students of the German education study program, textbooks have a very positive meaning for students. Keywords: Textbook Development, German Grammar, Strukturen Und Wortschatz, Metacognition Skills.